Reseña de Pinker, S. (1998). How the Mind Works, London, Penguin Books. - Eizaga, Bárbara (Pragmalingüística, 2011)
<!–[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> Se trata de una reseña de Pinker, S. (1998). How the Mind Works, London, Penguin Books.